Clinico-epidemiological and immunological characteristics of rickettsioses in a Sri Lankan patient cohort 2018–2023 - Nayana Gunathilaka; Nilmini Chandrasena; Hemantha Sudusinghe; Vidusha Nethsara Mudalpath; Deshaka Jayakody; Ranjan Premaratna (BMC Infectious Diseases)
Abstract Background Rickettsioses, caused by intracellular bacteria of the genera Rickettsia and Orientia, are transmitted to humans through arthropod vectors such as ticks, fleas, and mites. Over the past two decades, this disease has been recognized as a significant cause of acute febrile illness in Sri Lanka. However, only a limited number of studies have focused on clinico-epidemiological characteristics of patients and immunological diagnostic approaches for disease confirmation. Method A cross-sectional study was conducted at the Rickettsial Disease Diagnostic and Research Laboratory (RDDRL), University of Kelaniya, Sri Lanka, from 2018 to 2023 from the clinically suspected patients referred for disease confirmation. Clinical, demographic, epidemiological, biochemical, and laboratory data were collected via a questionnaire by reviewing the archived records. The serological finding of the immunofluorescence assay (IFA) conducted for patients samples were retrieved. The patients who were positive for IFA-IgG (> 1:128 as per presumptive confirmation of acute rickettsial illness) were taken as the test group and the negative group was taken as the control group. Data were analyzed using chi-square tests followed by a Correlation analysis between the variables using Pearson correlation. Results Out of 1,221 cases, 249 (20.4%) were serologically “confirmed” as positive for rickettsial infection. The test group consisted predominantly of males, similar to the control group. Most cases were males and < 9 years of age followed by 10–19 years. Among the age groups, 10–19 years and 50–59 years, categories indicated a significant positive relationship according to the chi-squared statistics (P < 0.05). A seasonal trend was observed, with higher case numbers reported from January to February. Laboratory findings indicated significant differences between test and control groups in leucopenia (P = 0.005, χ²=7.87), increased neutrophil count (P = 0.0004, χ²=12.71), elevated alanine aminotransferase (P = 0.0001, χ²=14.64), elevated aspartate aminotransferase (P = 0.0001, χ²=18.24), urine occult blood (P = 0.024, χ²=5.09), and raised erythrocyte sedimentation rate (P = 0.034, χ²=4.51). Clinical manifestations showed no major deviations. Notably, eschar was more prevalent in O. tsutsugamushi cases (33.3%) compared to SFG rickettsioses (13.3%). Conclusion This study highlights the need for improved awareness, diagnostic facilities, and vector control measures to manage rickettsial infections effectively in Sri Lanka. Understanding epidemiological patterns and clinical manifestations is crucial for developing effective surveillance and prevention strategies. Clinical trial Not applicable.